Social Media Da'wah as a Means to Deepen the Religious Understanding of Generation Z - Jalaluddin, Moh.; Siskawati, Isna; Kudrotullah, Aan; Uyun, Nadrotul; Eletmany, Mohamed R. (STAI Publisistik Thawalib Jakarta, 2024)
This study is significant as it addresses the need for contextual digital da’wah in a village with high media access but limited da’wah strategies and low digital religious literacy among youth through TikTok and Instagram. It explains the role of social media as a means of Islamic preaching to deepen religious understanding among Generation Z. This research employs a mixed-methods approach using observation, documentation, interviews, and survey techniques to analyze Generation Z’s responses to digital da’wah through data condensation, data presentation, conclusion drawing, and source triangulation. The findings reveal: (1) Generation Z prefers TikTok and Instagram for accessing da’wah content due to its short, visual, and relevant format. However, the level of digital interaction remains low and requires a more interactive approach. (2) Survey results show that Generation Z's da’wah strategies are effective through relaxed, humorous, relevant, and digitally adaptive approaches, with an average score of 4.688, indicating a positive impact. (3) The main challenges of digital da’wah for Generation Z include limited internet quota, low digital literacy, the risk of misinformation, and the need for more relevant da’wah content addressing youth issues such as bullying and identity crises through a more applicable psycho-educational approach. The conclusion highlights that Generation Z needs short, relevant, and interactive da’wah content supporting digital literacy to overcome challenges and religious misinformation.